2014
DOI: 10.1177/0363546514560155
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Long Head Biceps Tenodesis

Abstract: The incidence of biceps tenodesis has increased yearly from 2008-2011. Arthroscopic tenodesis has emerged as a more popular technique. Charges associated with the procedure have increased significantly. Significant regional variations in procedural incidences exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
91
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 62 publications
1
91
0
2
Order By: Relevance
“…Thus biceps shortening and extension potentially leading to cosmetic restrictions, muscular pain, and cramping are effectively prevented. 1,4,10 Modern implants for intraosseous interference screw fixation such as the forkedeyelet SwiveLock Tenodesis screw enable in situ tenodesis and do not require tenotomy and Krackow suturing of the tendon stump prior to tenodesis. Redundancy of extracorporeal LHBT exteriorization considerably simplifies the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus biceps shortening and extension potentially leading to cosmetic restrictions, muscular pain, and cramping are effectively prevented. 1,4,10 Modern implants for intraosseous interference screw fixation such as the forkedeyelet SwiveLock Tenodesis screw enable in situ tenodesis and do not require tenotomy and Krackow suturing of the tendon stump prior to tenodesis. Redundancy of extracorporeal LHBT exteriorization considerably simplifies the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…O ver the past few years, interest in tenodesis of the long head of the biceps tendon (LHBT) has continually increased particularly regarding minimally invasive and arthroscopic techniques. 1 Unsatisfactory high rates of cosmetic deformity, muscular fatigue, and cramping after tenotomy in view of steadily increasing patient demands contribute to this still ongoing trend.…”
mentioning
confidence: 99%
“…Several studies have shown increased use of BT over the past decade, often in conjunction with rotator cuff repair, subacromial decompression, or distal clavicle excision. [3][4][5] The recent paradigm shift toward more minimally invasive or arthroscopic surgery within the past 2 decades has given way to innovative methods for managing bicepsesuperior labral complex pathology.…”
Section: See Related Article On Page 23mentioning
confidence: 99%
“…T o minimize cramping and cosmetic deformity with biceps tenotomy, the number of biceps tenodesis procedures is rising. 1 In orthopaedic procedures such as rotator cuff repair, distal biceps repair, and quadriceps tendon repair, tendon-to-bone fixation is often recommended to create a more reliable healing response. So why do many surgeons advocate soft-tissue fixation over bony fixation for proximal biceps tenodesis?…”
Section: See Related Article On Page 560mentioning
confidence: 99%